Duration of insomnia and success expectancy predict treatment outcome of iCBT for insomnia - Pchelina, Polina; Poluektov, Mikhail (Frontiers in Sleep, 2024)
The identification of the prognostic factors of treatment outcome may assist in customizing the intervention to the patient's needs. Hence, we have conducted a secondary analysis of data from a randomized controlled trial investigating the effectiveness of an internet-based cognitive behavioral therapy for insomnia (iCBT-I) aiming to find patients' characteristics that may predict the change of insomnia severity after treatment.In this exploratory analysis, involving 94 chronic insomnia patients, we examined the predictive value of several self-reported measures, medical history, and sociodemographic variables to psychological distress with separate linear regression models. The main outcome was the Insomnia severity index (ISI) improvement from pre-to post-treatment: The study found that duration of insomnia [b (SE) = -0.02 (0.01), p = 0.01] and attitudes about the expected treatment success [b (SE) = 0.80 (0.27), p = 0.004] were predictors of a better outcome. Moreover, better outcome was associated with the lower level of traits of attention seeking [b (SE) = -1.06 (0.51), p = 0.04] and grandiosity [b (SE) = -1.50 (0.57), p = 0.01], distractibility [b (SE) = -1.57 (0.75), p = 0.04] and rigid perfectionism [b (SE) = -1.32 (0.65), p = 0.05].Our results suggest that iCBT-I might be particularly beneficial for patients with higher expectations from the therapy and those who have a shorter duration of insomnia. Some pronounced personality traits, like attention seeking, grandiosity, distractibility, and rigid perfectionism may predict worse outcomes. However, since this was a post hoc analysis, our results must be considered exploratory and verified in further studies